Similarity and Phylogenetic Analysis of Herbicide-Resistant Goosegrass (Eleusine indica) Biotypes - Koko Tampubolon; Fransisca Natalia Sihombing; Elseria Siburian; Yustina Sri Sulastri; Zavandri Purba; Sony Tri Septian Samosir; Syahibal Karim (Caraka Tani: Journal of Sustainable Agriculture, 2019)
Molecular approach as a herbicide-resistant agent detector is an initial solution before controlling of Eleusine indica weed. This review article is aimed to obtain the basic data of similarity and phylogenetic values among herbicide-resistant E. indica biotypes. This research used a descriptive analytical method. The analysis involved 14 nucleotide sequences of herbicide-resistant E.indica biotypes obtained from the National Center for Biotechnology Information. The nucleotide alignment of herbicide-resistant E. indica biotypes was conducted with ClustaLW using the Molecular Evolutionary Genetics Analysis (MEGA) v. 5.05 software based on a method of neighbor-joining tree construct/test. The results showed that two nucleotides of 7,921 herbicide-resistant E. indica biotypes were homologous (sequence 1,231 and sequence 1,408). The similarity values among herbicide-resistant E. indica biotypes ranged from 0.00 to 1.19. The information of phylogenetic pattern is needed in the selection of the herbicides mode of action rotation in order to control herbicide-resistant E. indica biotypes.